Reduced salinity exacerbates the viral infection on the coccolithophorid Emiliania huxleyi at elevated pCO2 - Fu, Qianqian; Gao, Kunshan (Frontiers in Marine Science, 2022)
The blooms of coccolithophores are usually terminated by their viruses. However, little has been documented on the interplay between the host with virus under different environmental conditions. We investigated the relationship of Emiliania huxleyi (BOF92) and its virus (EhV99B1) after the coccolithophorid had acclimated to different levels of salinity (S35: 35‰; S25: 25‰) and CO2 (AC: 400 μatm; HC: 1000 μatm) for about 15 generations. Our results showed that the virus infection decreased the growth of E. huxleyi along with decreased photochemical efficiency and photosynthetic carbon fixation under all the combinations of the treatments. Lowered salinity exacerbated the impacts of the viral infection on the growth and photosynthetic performance of E. huxley. The elevated pCO2 appeared to have alleviated the impacts of the viral infection on its photosynthetic performance with enhanced levels of Fv/Fm, by about 49% under S35 and by about 16% under S25, respectively. Nevertheless, the elevated pCO2 enhanced the virus burst size by about 18% under the high and by about 46% under the low levels of salinity, respectively. It is concluded that reduced salinity under the elevated pCO2 exacerbates the impact of the virus on E. huxleyi, leading to the highest burst sizes and the lowest photosynthetic carbon fixation, and the enhanced photochemical efficiency and increased levels of Chl a under the elevated pCO2 could have facilitated the energy supply for the virus multiplication in the infected cells of E. huxleyi.